Current exposure to phthalates and DINCH in European children and adolescents - Results from the HBM4EU Aligned Studies 2014 to 2021 - Vogel, Nina; Schmidt, Phillipp; Lange, Rosa; Gerofke, Antje; Sakhi, Amrit K; Haug, Line S; Jensen, Tina Kold; Frederiksen, Hanne; Szigeti, Tamás; Csákó, Zsófia; Murinova, Lubica Palkovicova; Sidlovska, Miroslava; et al. (International journal of hygiene and environmental health, 2023)
Phthalates are mainly used as plasticizers for polyvinyl chloride (PVC). Exposure to several phthalates is associated with different adverse effects most prominently on the development of reproductive functions. The HBM4EU Aligned Studies (2014-2021) have investigated current European exposure to ten phthalates (DEP, BBzP, DiBP, DnBP, DCHP, DnPeP, DEHP, DiNP, DiDP, DnOP) and the substitute DINCH to answer the open policy relevant questions which were defined by HBM4EU partner countries and EU institutions as the starting point of the programme. The exposure dataset includes ∼5,600 children (6-11 years) and adolescents (12-18 years) from up to 12 countries per age group and covering the North, East, South and West European regions. Study data from participating studies were harmonised with respect to sample size and selection of participants, selection of biomarkers, and quality and comparability of analytical results to provide a comparable perspective of European exposure. Phthalate and DINCH exposure were deduced from urinary excretions of metabolites, where concentrations were expressed as their key descriptor geometric mean (GM) and 95th percentile (P95). This study aims at reporting current exposure levels and differences in these between European studies and regions, as well as comparisons to human biomonitoring guidance values (HBM-GVs). GMs for children were highest for ∑DEHP metabolites (33.6 μg/L), MiBP (26.6 μg/L), and MEP (24.4 μg/L) and lowest for∑DiDP metabolites (1.91 μg/L) and ∑DINCH metabolites (3.57 μg/L). In adolescents highest GMs were found for MEP (43.3 μg/L), ∑DEHP metabolites (28.8 μg/L), and MiBP (25.6 μg/L) and lowest for ∑DiDP metabolites (= 2.02 μg/L) and ∑DINCH metabolites (2.51 μg/L). In addition, GMs and P95 stratified by European region, sex, household education level, and degree of urbanization are presented. Differences in average biomarker concentrations between sampling sites (data collections) ranged from factor 2 to 9. Compared to the European average, children in the sampling sites OCC (Denmark), InAirQ (Hungary), and SPECIMEn (The Netherlands) had the lowest concentrations across all metabolites and ESTEBAN (France), NAC II (Italy), and CROME (Greece) the highest. For adolescents, comparably higher metabolite concentrations were found in NEB II (Norway), PCB cohort (Slovakia), and ESTEBAN (France), and lower concentrations in POLAES (Poland), FLEHS IV (Belgium), and GerES V-sub (Germany). Multivariate analyses (Survey Generalized Linear Models) indicate compound-specific differences in average metabolite concentrations between the four European regions. Comparison of individual levels with HBM-GVs revealed highest rates of exceedances for DnBP and DiBP, with up to 3 and 5%, respectively, in children and adolescents. No exceedances were observed for DEP and DINCH. With our results we provide current, detailed, and comparable data on exposure to phthalates in children and - for the first time - in adolescents, and - for the first time - on DINCH in children and adolescents of all four regions of Europe which are particularly suited to inform exposure and risk assessment and answer open policy relevant questions.
Keywords: kyseliny ftalové; Phthalic Acids; Phthalates; Adolescents; DINCH; Adolescent; Child; látky znečišťující životní prostředí; dítě; mladiství; Children; lidé; HBM; Exposure; Humans; Environmental Exposure; Environmental Pollutants; HBM4EU; vystavení vlivu životního prostředí